Calcite growth in Cissus quadrangularis plant extract, a traditional Indian bone-healing aid - Sanyal, A.; Ahmad, Absar; Sastry, M. (Current Science, 2005)
Cissus quadrangularis, a plant that has been customarily used in the Indian subcontinent to hasten the process of healing in bone fractures, has been studied and exploited to synthesize calcite crystals. The plant extract serves as a rich source of calcium ions, which when reacted with CO2, leads to the formation of calcite crystals of highly irregular morphology indicating that bioorganic molecules present in the extract modulate the crystal morphology.
Keywords: bone fracture; calcite crystals; Cissus quadrangularis; traditional healing

Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Controlling the optical properties of lemongrass extract synthesized gold nanotriangles and potential application in infrared-absorbing optical coatings - Shankar, S. S.; Rai, A.; Ahmad, Absar; Sastry, M. (Chemistry of Materials, 2005)
Anisotropic metal nanoparticles have distinct optical behavior when compared with their spherical counterparts. In this report, we demonstrate a simple method involving the reduction of aqueous gold ions by the extract of the lemongrass plant leading to the formation of gold nanotriangles with interesting absorption in the near-infrared (NIR) region of the electromagnetic spectrum. We show that, by simple variation of the experimental conditions, it is possible to vary the size of the gold nanotriangles and, thus, to tune the absorbance of flat gold nanoparticles in the NIR region. The NIR absorption of the gold nanotriangles is expected to be of application in hyperthermia of cancer cells and in IR-absorbing optical coatings. We show that the lemongrass extract synthesized gold nanotriangles can be easily cast in the form of films on glass substrates and that these films are highly efficient in absorbing IR radiation for potential architectural applications.